Chronic Constipation in the Elderly: An Unusual Presentation of Colonic Dysmotility in an Elderly Patient - R. Peravali; H. Kranenburg; J. E. Martin; N. Keeling (Case Reports in Surgery)
Introduction. Chronic constipation is common in the elderly, and often no underlying pathology is found. Primary colonic dysmotility has been described in children but is rare in the elderly. Case report. We present an 82-year-old female with long standing constipation presenting acutely with large bowel obstruction. Laparotomy and Hartman’s procedure was performed, and a grossly distended sigmoid colon was resected. Histology revealed a primary myopathic process. Conclusion. Primary colonic myopathy should be considered in elderly patients presenting with large bowel obstruction and a long preceding history of constipation, particularly when previous endoscopic examinations were normal.